Prevalence of metastasis in T1b esophageal squamous cell carcinoma: a retrospective analysis of 258 Chinese patients - Qi, Xiaotong; Li, Mingna; Zhao, Sheng; Luo, Jinhua; Shao, Yongfeng; Zhang, Zhihong; Chen, Yijiang (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: There is controversy regarding the impact of different depths of submucosal invasion on lymph node metastasis (LNM) and overall survival (OS). We evaluated the impact of depth of submucosal invasion on the presence of metastatic lymphadenopathy and survival in a Chinese population with esophageal squamous cell carcinoma (ESCC). Methods: A total of 258 patients who underwent esophagectomy from November 2009 to March 2014 were studied. Demographics of patients, tumor characteristics, and surgical information were retrospectively collected through medical records. Submucosal invasion was equally categorized into inner one-third (sm1), middle one-third (sm2), and deep one third (sm3) invasion by pathologists. The patients were observed at the outpatient department in accordance with appointed time and recurrence, and deaths were recorded. The median follow-up duration was 26 months and the deadline was April 2015. Cancer characteristics and its association with LNM and OS were analyzed. Results: The study included 75 (29.1%) sm1, 73 (28.3%) sm2, and 110 (42.6%) sm3 patients, and the rates of LNM were 12% (9/75), 11% (8/73), and 20.9% (23/110), respectively. sm3 might be associated with regional LNM (univariate analysis, P=0.041). Tumor volume >1.856 cm3 (P=0.022) and lymphovascular invasion (LVI) (P=0.004) predicted LNM using multivariate analysis. No significant differences in distant metastases were observed according to the depth of invasion. Only metastatic lymph nodes predicted OS (P